Anterior skull base tumors - Nicolai, Piero 1954-; Bradley, Patrick J. 1949- (Basel : Karger, 2020)
In recent years, interest in the management of anterior skull base tumors has been fostered by the introduction and subsequent rapid expansion of indications of transnasal endoscopic techniques. In parallel, extraordinary progress has been made in all the other disciplines which are involved in the complex process of managing anterior skull base tumors, leading to substantial improvements in diagnosis and treatment. The anterior skull base can be involved in a large variety of tumors of a varying nature and histology, which in the majority of cases originate from adjacent anatomic sites. In fact, primary lesions of the anterior skull base mainly include osteoma and other tumors originating from bone and cartilage. Tumors involving the anterior skull base have their origin prevalently in the sinonasal tract, but lesions developing on the intracranial site, such as meningiomas, may also extend caudally to encroach upon this area. All these lesions are rare, which means that the pertinent literature does not include prospective studies or treatment guidelines based on a high level of evidence. In view of the extreme histological variability of lesions involving the anterior skull base, much emphasis has been placed on addressing the different nuances of treatment in relation to histology, especially for malignant tumors. The chapters focusing on surgery provide divergent views on selection criteria for a specific surgical technique, which is the aim of this publication.
Keywords: BASE DEL CRANEO -- NEOPLASMAS; BASE DEL CRANEO -- NEOPLASMAS -- DIAGNÓSTICO; BASE DEL CRANEO -- NEOPLASMAS -- TRATAMIENTO